Cuirass Ventilation: An Alternative Home-Based Modality for Chronic Respiratory Failure. Issue 1 (February 2020) - Onweni, Chidinma; Rashid, Saima; Goswami, Rachna; Treece, Jennifer; Shipley, Lindsey C.; De Souza, Randal; O'Neill, Luke; Simberloff, Tander; Baumrucker, Steven J.
The biphasic cuirass ventilation (BCV) device is an alternative respiratory support device for patients with chronic respiratory failure. Considered by some a "forgotten" mode of supportive ventilation, the device is portable, lightweight, and easy to operate. Biphasic cuirass ventilation can also be used to rapidly resuscitate patients in acute respiratory distress and requires minimal technical skill to operate. Biphasic cuirass ventilation can be employed by the patient's caregiver in the home setting, making it a viable alternative to other forms of mechanical ventilation (e.g., BiPAP) for patients enrolled in home hospice or palliative care. The article reviews current knowledge and aims to enhance awareness and encourage further study about cuirass ventilation, particularly with regard to its use in treating patients in the palliative care setting and in the home.